How does the government improve the competitiveness of SMEs? lesson learned from Thailand - Andrie Elia; Basrowi Basrowi; Buncha Chinnasri (Otoritas : Jurnal Ilmu Pemerintahan, 2023)
The purpose of this study is to describe the strategy pursued by the Government of Thailand in collaboration with existing stakeholders in increasing the competitiveness of SMEs amidst the invasion of foreign manufacture-based products. The method used is observation and in-depth interviews at SME product canters, SME product marketing places in tourist destinations, and related parties. Observations were made for 5 years 2018-2023, however, in-depth observations were made in January-March 2023. The results of the analysis show that the competitiveness of SMEs in Thailand is very good due to support from universities, private businessmen (Ventura capital), the government: (innovation support organizations, and state-owned entrepreneurs), large companies in the form of CSR, and various parties who are very concerned about advancing SMEs. SMEs that already have high competitiveness with quality products, will be encouraged to move up to a class that is ready to export. Only SMEs that already have "four stars" are allowed to export because the quality of their products is beyond doubt and can even be proud of.